Relevansi Nilai dan Determinan Pengungkapan Modal Intelektual - Rinto Hamonangan; Carmel Meiden (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2020)
In recent decades users have emphasized that traditional financial reporting is beginning to lose the relevance of the value of earnings and the book value of equity. To cover these weaknesses, investors began to look for other information to make investment decisions. Intellectual capital is included in the top ten in the information needed by information users. Intellectual capital is a potential source for modern companies to gain competitive advantages that are difficult for competitors to imitate and drive business development and success in the future. This study aims to examine the value relevance of disclosure of intellectual capital information on traditional industrial and non-traditional companies, and examine what factors influence companies to disclose intellectual capital. Using the purposive judgment sampling method, the company sample consisted of 68 companies from various types of industries that were listed on the Indonesia Stock Exchange in 2014-2018. The results is disclosure of intellectual capital has value relevance in traditional companies, but in non-traditional companies there is not enough evidence found that disclosure of intellectual capital has value relevance. Company age, audit quality, market book ratio, company size, and type of industry have a strong influence on intellectual capital disclosure. Whereas leverage and profitability have no influence on intellectual capital disclosure. Keywords : intellectual capital, intellectual capital disclosure, firm age, traditional industry, non- traditional industry